Orientalisme Edward Said dalam Novel Kereta Semar Lembu Karya Zaky Yamani - Kisma Pradahati; Dwi Susanto (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The aim of this study is to analyze the representation of orientalism in the novel Kereta Semar Lembu by Zaki Yamani (2022), using Edward Said's theory. Orientalism is understood as a discourse created by the West to establish and maintain its superiority over the East. This study employs a qualitative-descriptive method using observe and note technique. The study focuses on three main aspects: (1) discrimination against the local (pribumi) people, (2) the construction of superiority and inferiority between the West and the East, and (3) the practice of domination by Western (Dutch) powers over the Eastern (Indonesian) people. Data were obtained from narrative excerpts in the novel that portray colonial power relations and representational strategies of the East. The analysis shows that colonial domination occurred not only physically, such as through the exploitation of labor and agrarian resources, but also symbolically through language, social systems, education, and cultural values. Indigenous characters are reduced to backward, irrational, and passive figures, while European characters are depicted as symbols of rationality and progress. Thus, the novel can be interpreted as a critique of colonialism and the hegemonic discourse of the West over the East.  Keywords: Orientalism; Colonialism; Discrimination